The Effect of Dysglycaemia on Changes in Pulmonary and Aerobic Function in Cystic Fibrosis - Tomlinson, Owen W.; Stoate, Anna L. E.; Dobson, Lee; Williams, Craig A. (Frontiers in Physiology, 2022)
Cross-sectional studies have reported lower pulmonary and aerobic function during exercise in people with cystic fibrosis related diabetes (CFRD), compared to non-CFRD counterparts. However, this association has yet to be investigated longitudinally and therefore this study examines these differences over time between people with cystic fibrosis (CF) of differing glycaemic status. Annual review data, including cardiopulmonary exercise tests and pulmonary function tests, were retrospectively analysed at baseline (T0, n = 82) and at a one-year follow-up (T1, n = 54). Data was analysed in 3 groups: normal glucose tolerance (NGT), impaired glucose tolerance (IGT) and CFRD. Further analyses were undertaken, with a dichotomous split of NGT and a combined IGT/CFRD group. At baseline, a significant reduction in the majority of variables, including forced expiratory volume in one second (FEV1) and maximal oxygen uptake (VO2max), was observed in the CFRD (n = 19) group compared to NGT (n = 58). At follow-up, no significant differences were observed, and no interaction effect between CFRD status and time was identified. FEV1 and VO2max presented with varying directions and magnitudes of change within patients. In summary, patients with CFRD have a reduced aerobic and pulmonary function compared to non-CFRD counterparts, although such changes disappeared at follow up. Varying responses for FEV1 and VO2max highlight the need to consider both variables as independent markers of function in CF.